INTERFACE AND SOFTWARE FOR OSCILLOSCOPE COMPARATOR - Udovichenko, S. N. (Одеські астрономічні публікації, 2017)
For measurement of photographic spectrograms on the comparator with the oscilloscopic guidance on line are used photoelectric moire measuring detector of linear movement of carriage with measuring plate and reversible binary-decade digit counters, which interfaced with the personal computer IBM PC. Automatic input of the current comparator count and control of cutting slits motion are carried out by means of a parallel interface board. The comparator software works is designated to make reduction of ordinary and zeeman photospectrograms.